Trade agreement, innovation and survival of processed food export in Malaysia - Idris, Afiza (2021)
Over the past decade, processed food export of Malaysia has recorded buoyant growth. However, recent evidence showed that it was losing competitiveness. Excluding palm oil exports, Malaysia even lagged behind its peer countries in the ASEAN region. In order to gain greater market access, many countries including Malaysia, have increasingly used trade policy tools in the form of free trade agreements. In addition, enhancing innovation has been widely accepted as an important strategy to boost economic growth and increase exports. However, there are limited studies on the impact of trade agreements ratified by Malaysia and innovation activities on the performance of processed exports. To the best of our knowledge, there is hardly any study on the export survival of processed food products in Malaysia. Therefore, against this backdrop, the objectives of the study are to examine on the effect of trade agreements on the performance of processed food exports, investigate the impact of innovation on export margins, and identify the factors that influence its export survival. The study examined exports of processed food for a period of 18 years from 2000 to 2017 and used panel data from 32 countries. The gravity model was used to investigate on the impact of trade agreements. The study found that trade agreements ratified by Malaysia at the regional level, namely the ASEAN bilateral FTAs with China, India, Japan, Korea, and Australia and New Zealand led to export creation and expansion for Malaysia’s processed food. The study did not show any evidence of export diversion. The magnitude of impact varied according to product groups and each FTA. In addition, gravity model was also used to examine the impact of innovation input and output on export margins. The study showed that Malaysia’s export growth of processed food was mainly due to the intensive margin. In terms of innovation input, R&D intensity showed a positive impact on extensive and intensive margins up to a certain threshold before it declined. This was linked to the non-linear relationship between R&D intensity and export margins. The impact of patents, which is a proxy for innovation output, was found to be insignificant, while trademarks showed a small positive impact. The study also found that the processed food exports had a short survival time, in line with findings from previous studies on export duration. Using the Kaplan-Meier estimator, the median survival time for processed food export flow was only 2 years. The export survival rate and duration varied according to product type and market location. Export survival time was found to be longer and more persistent in the ASEAN and East Asia Pacific (EAP) regions. Furthermore, the larger the initial export value, the longer the survival time and rate. The Cox Proportional Hazard and the random effects logit model results showed that market size and free trade agreements were statistically significant in reducing the hazard of export failures, while vice-versa for distance and population of importing countries. Overall, this study recommends ratification of trade agreements to stimulate exports of processed food and improve export survival. Closer integration among countries of the ASEAN region and its other key partners should be forged, particularly using RTA format that takes into consideration specific industry needs. In addition, the design of future RTAs and bilateral FTAs should cater for enhancing market access of new product varieties, which may require industry foresight studies. Meanwhile, R&D and targeted FDI should be enhanced in the food processing industry to stimulate product variety and export growth. Given the short export survival time, export promotion and assistance schemes will need to be customised according to different market needs and extended to exporters beyond the average survival time to ensure better export survival rate.